2018
DOI: 10.1186/s12885-018-4117-z
|View full text |Cite
|
Sign up to set email alerts
|

Real life patterns of care and progression free survival in metastatic renal cell carcinoma patients: retrospective analysis of cross-sectional data

Abstract: BackgroundPatient characteristics and survival outcomes in randomized trials may be different from those in real-life clinical practice. The objective of this study was to describe treatment pathways, safety, drug costs and survival in patients with metastatic Renal Cell Carcinoma (mRCC) in a real world setting.MethodsA retrospective analysis was performed using IQVIA real world oncology cross-sectional survey data, a retrospective treatment database collecting anonymized patient-level data in Europe. Data on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 21 publications
2
17
1
Order By: Relevance
“…Cancer November 15, 2019 The stronger correlation between OS and rwTTD compared with OS and rwPFS differs from typical cytotoxic therapy findings. 20 This could reflect the practice of treatment beyond RECIST-defined progression, because OS and rwTTD capture the benefit of the additional immunotherapy exposure, but rwPFS does not; further research is ongoing.…”
Section: Continuedmentioning
confidence: 77%
See 4 more Smart Citations
“…Cancer November 15, 2019 The stronger correlation between OS and rwTTD compared with OS and rwPFS differs from typical cytotoxic therapy findings. 20 This could reflect the practice of treatment beyond RECIST-defined progression, because OS and rwTTD capture the benefit of the additional immunotherapy exposure, but rwPFS does not; further research is ongoing.…”
Section: Continuedmentioning
confidence: 77%
“…The estimated median rwPFS in this cohort was similar to that observed in all pivotal PD‐(L)1 inhibitor trials, except for 1 trial that was restricted to patients without an EGFR mutation or ALK rearrangement. PFS concordance between real‐world patients and traditional clinical trial cohorts has also been observed before . rwPFS, an intermediate endpoint, may be linked more closely to treatment effect than to OS, because OS inherently captures the impact of all subsequent therapies administered to the patient after the PD‐(L)1 inhibitor‐containing regimen.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations